Awareness and Mental Health of Male Drug Addicts With Tuberculosis During the COVID-19 Pandemic - Jia, Dongming; Li, Hai; Xu, Yuming (Frontiers in Psychiatry, 2021)
Introduction: At present, the COVID-19 pandemic remains the most pressing global health issue. Given the significant amount of public awareness, the infection rate and rehabilitation efforts are governed not only by the compliance of transmission mitigation strategies but also by the understanding of coexisting diseases and COVID-19 in patients with chronic infectious diseases. The main goal of this study was to evaluate the differences in demographics, as well as awareness, risk perception, and emotional reactions, among imprisoned drug addicts with and without tuberculosis (TB) regarding their perceptions of and feelings toward the COVID-19 pandemic. The secondary goal of the study was also to measure how the psychological health and nutritional indices of the drug addicts with TB changed during their ongoing rehabilitation. Methods: A total of 265 male drug addicts, 45 of which were positive for TB and another 220 who were negative, were selected as subjects from a mandatory detoxification and rehabilitation center (MDRC). Data were collected through a combination of questionnaires (questions regarding COVID-19 awareness, emotional knowledge and responses, and SCL-90 tests), anthropometric examination, and laboratory blood tests, with which inferential and descriptive statistical analyses were performed. Results: During a period of 1 week in early 2021, the differences in the accuracy of the responses from the questions probing the awareness of COVID-19 symptoms, transmission, susceptible populations, what kind of mask should be worn, and preventive measures between TB addicts to non-TB addicts were 11.11 vs. 60.45%, 57.78 vs. 77.27%, 66.67 vs. 78.64%, 97.98 vs. 97.73%, and 93.33 vs. 65.91%, respectively. In the risk perception and emotional reaction sections of the questionnaire, there was a significant difference in the responses to “What you were more worried about was?” (p < 0.001) and “Alteration in your mood since the outbreak?” (p = 0.002) between the two cohorts. In the section assessing the 10 dimensions of the SCL-90 scale, there were significant differences between the TB addicts and the Chinese norm. In addition, the BMI (21.06 ± 2.65 kg/m2) and total serum protein (77.14 ± 6.12 g/L) levels of the TB addicts were normal, but the serum hemoglobin (117.02 ± 4.97 g/L) and albumin (42.08 ± 1.81 g/L) levels were significantly lower in the TB addicts compared to the norm (p < 0.001). Conclusion: The COVID-19 pandemic we are facing is both an epidemiologic and a psychological crisis. However, while the COVID-19 epidemic will eventually disappear (or become manageable, similar to the flu), the TB epidemic may still persist. To avoid the deleterious consequences of multiple simultaneous epidemics, complementary response measures to COVID-19 and TB can help curb the exacerbation of both situations and, therefore, save lives. Imprisoned drug addicts, especially those with TB, can master relevant knowledge on COVID-19.